Women’s Expectations and Satisfaction with Intrapartum Care - Pareigytė, Justina; Vaškelytė, Alina (Slauga. Mokslas ir praktika, 2020)
The aim of the study. To analyse women’s expectations and satisfaction with intrapartum care. Methods. The research was conducted in February 2019–January 2020 on several online websites – manoapklausa.lt, supermama.lt and tevudarzelis.lt. The research scope included women, who have given birth in the recent five years, making a total of 494 women, who have given birth. The scientific research data was collected using an intrapartum-specific QPP – questionnaire (QPP-I), which is used particularly for intrapartum care assessment. Results and conclusions. Women giving birth for the first time scored significantly higher on their expectations, compared to their satisfaction with intrapartum care in terms of medical-technical competence, physical-technical conditions, person-centred approach, social and cultural environment. Women giving birth not for the first time also showed significant differences between their expectations and satisfaction with intrapartum care in terms of medical-technical competence, physical-technical conditions, person-centred approach, social and cultural environment. A comparison of the expectations of those, who have given birth for the first time and not showed that the expectations in terms of medical-technical competence, also social and cultural environment were significantly higher in those, who have given birth for the first time than those, who have given birth for the second and more times. Both research groups showed similar satisfaction with intrapartum care.